Pan-cancer analysis of FBXW family with potential implications in prognosis and immune infiltration - Huang, Tingting; OuYang, XIaoxiao; Li, Jiwei; Shi, Bingbing; Shan, Zhengda; Shi, Zhiyuan; Yang, Zhangru (Frontiers in Immunology, 2022)
The F-box and WD repeat domain containing (FBXW) family of E3 ligases has 10 members that are responsible for ubiquitination and degradation of substrate proteins involved in cell cycle regulation and tumorigenesis. Among them, FBXW1 (also called β-TrCP1/ BTRC) and FBXW7 are the central proteins in this category. However, there is still a lack of comprehensive understanding of the contribution of FBXW family members, especially FBXW1 and FBXW7, in various tumor types. In this present study, we preliminarily analyzed the genetic structure characteristics of the FBXW family, and systematically investigated their expression patterns and clinical correlations based on the TCGA pan-cancer data. As a result, there were obvious genetic heterogeneity and different clinical traits in FBXW family members. Moreover, we found that FBXW family genes may be useful in predicting prognosis and therapeutic efficacy using survival analysis. In addition, the immune infiltration of FBXW family was also clearly illustrated in this study. The results showed these genes were closely involved in immune components such as immune score, immune subtypes, tumor-infiltrating lymphocytes and immune checkpoints. Notedly, FBXW1 as an oncogene and FBXW7 as a tumor suppressor gene also show opposite relationships on immune cells. Collectively, our results provided valuable strategies to guide the therapeutic orientation concerning the role of FBXW family genes in cancer.